TINJAUAN HUKUM INTERNASIONAL MENGENAI ASEAN OPEN SKY DAN DAMPAKNYA BAGI INDONESIA - Heike Larissa Tampubolon; Arif Arif; Chairul Bariah (Journal of USU International Law, 2013)
Abstract Aircraft is known as the most effective means transportation at this time. Start in terms of safety, comfort, economy, and the time when compared with other means of transportation such as land and sea transportation. By using aircraft, as if there are no more boundaries between regions of the country to another. Since the number of positive benefits, then the air transport becomes very important in human life and even the country. One country to enter into agreements with other countries by exchanging the rights of freedom in the air. ASEAN Open Sky is one form of multilateral agreements between countries which aims to realize the ASEAN aviation liberalization in the ASEAN region. The liberalization of the concept will be realized in 2015. It is expected there will be positive impacts for Indonesia and ASEAN by following the liberalization of the flight. For negative impacts, Indonesia and other ASEAN countries are required to start paying attention and taking into account all possibilities that will happen, so that negative impacts can be avoided and it can be turned into a positive impact. Keywords  : flight, country, liberalization